1985
DOI: 10.1017/s0043174500083016
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Red Rice (Oryza sativa) with Rice (O. sativa)

Abstract: Red rice (Oryza sativaL. ♯ ORYSA) densities of 5, 108, and 215 plants/m2reduced grain yield of commercial rice (Oryza sativaL.) 22, 77, and 82%, respectively. At a cultivated rice density of 195 plants/m2, red rice at 5, 108, and 215 plants/m2reduced straw dry weight of cultivated rice 18, 66, and 68%, respectively. At a red rice density of 5 plants/m2, reduction in number of cultivated rice grains per panicle ranged from 8 to 18%, whereas densities of 108 and 215 plants/m2reduced grains per panicle 56 to 70%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0
2

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 14 publications
5
64
0
2
Order By: Relevance
“…The remaining red rice biotypes had either the same or a lower number of tillers than CLXL8 rice. The number of tillers produced by red rice can change significantly depending on the planting density of cultivated rice or red rice (Diarra et al 1985). When these 12 red rice biotypes were grown in noncompetitive conditions, the tiller numbers were three to five times higher than those observed in this experiment (Shivrain 2004).…”
Section: Impact Of Red Rice Biotypes On Yields Of Different Ricementioning
confidence: 55%
See 1 more Smart Citation
“…The remaining red rice biotypes had either the same or a lower number of tillers than CLXL8 rice. The number of tillers produced by red rice can change significantly depending on the planting density of cultivated rice or red rice (Diarra et al 1985). When these 12 red rice biotypes were grown in noncompetitive conditions, the tiller numbers were three to five times higher than those observed in this experiment (Shivrain 2004).…”
Section: Impact Of Red Rice Biotypes On Yields Of Different Ricementioning
confidence: 55%
“…Some red rice biotypes show more vigorous emergence than others and can produce much aboveground dry matter yield in early plantings (Gealy et al 2000). Previous research on red rice emergence (Gealy et al 2000) and cultivated rice yield losses mostly involved competition with strawhull red rice and only at one planting time (Diarra et al 1985;Kwon et al 1991;Ottis et al 2005;Zhang et al 2006). Planting time effects on red rice emergence and competition dynamics of cultivated and red rice are unknown.…”
mentioning
confidence: 99%
“…Also, the same infestation of 20 red rice plants/m 2 will contaminate the commercial grain harvested with about 1100 kg/ha of red rice grain (Figure 6), reducing its quality and price. Red rice can shatter more seed than found in this experiment; up to 70% was reported by Diarra (1985b). This potential for reinfesting rice fields and lowering rice quality should be considered when information such as that in Figure 4 is used to derive economic thresholds to manage red rice.…”
Section: Density and Duration Of Red Rice Infestationsmentioning
confidence: 70%
“…Diarra (1985b) found that red rice densities of 5, 108, or 215 plants/m 2 reduced grain yields of rice by 22%, 77%, or 82%. In southern Brazil 170 red rice panicles/m 2 (approximately 60 plants/m 2 ) reduced rice yield by 50% (De Souza, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…'Mars' also was a better competitor with red rice {Oryza sativa) than 'Lebonnet' (Diarra et al, 1985). 'Mars' also was a better competitor with red rice {Oryza sativa) than 'Lebonnet' (Diarra et al, 1985).…”
Section: Rice (Oryza Sativa)mentioning
confidence: 96%